Why are programmes for offenders with personality disorder not informed by the relevant scientific findings? - Duggan, Conor (The Royal Society, 2008)
This paper examines the evidence to justify intervening in those with personality disorder, specifically antisocial personality disorder (ASPD) as defined by the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV, American Psychiatric Association 1994). The evidence from randomized controlled trials in the mental health literature is reviewed and found to be deficient with only five trials satisfying Cochrane criteria, all of which had a reduction in substance misuse as their primary outcome, rather than a change in the personality disorder per se. Next, I consider the contribution of Thomas Kuhn to explain why it is difficult to develop a scientific basis in forensic mental health. I argue that, because forensic mental health is inclusive in its purpose (interacting with the law, social services and the penal system, all of which have different rules and agendas), it is difficult to develop a consensus on fundamentals, this consensus being a hallmark of a science. Finally, I argue that despite the absence of evidence from mental health, providers for ASPD are in a fortunate position in being able to draw upon the correctional literature. This is relevant, provided that we agree that a reduction in offending is the primary outcome. While mental health can learn much from correctional practice, it can also enhance the efficacy of the latter by, for instance, drawing attention to the specific vulnerabilities of the personality structure that might impede programme delivery in correctional settings. Means of achieving a conjunction of mental health and correctional practice are urgently required as this would be beneficial to both.